Differentiation-dependent glycosylation of cells in squamous cell epithelia detected by a mammalian lectin - Plzák, Jan; Holíková, Zuzana; Smetana, Karel; Dvoránková, Barbora; Hercogová, Jana; Kaltner, Herbert; Motlík, Jan; Gabius, Hans-Joachim (Cells, tissues, organs, 2002)
UNLABELLED: The squamous stratified epithelia contain a proliferative (harboring mitotic activity) and a differentiating compartment. Due to the potential of protein-carbohydrate interactions to regulate cellular activities we introduced a mammalian lectin to cyto- and histochemical analysis. We answer the questions of whether and to what extent this new probe can pinpoint differentiation-dependent glycosylation changes in sections and in culture of keratinocytes. MATERIAL AND METHODS: Purification and labeling enabled monitoring of galectin-3 reactivity in frozen sections of human and pig epidermis and basal cell carcinomas as well as in culture of keratinocytes. The staining pattern of the lectin was correlated with the staining profile of other cell markers including desmosomal proteins, beta(1) integrin, and the proliferation marker Ki-67. The Dolichos biflorus agglutinin (DBA) sharing binding reactivity of galectin-3 to the A type histoblood group epitope was used for comparison. RESULTS: Both lectins exhibit suprabasal binding. However, their profiles were not identical, substantiated by lack of coinhibition. Strong DBA reactivity was also observed in a limited number of basal layer cells, namely in cells without the expression of the proliferation marker Ki-67. Cultured mitotic epidermal cells have no reactivity for DBA. Presence of ligands for this plant lectin was connected with decreased positivity of nuclei for Ki-67 and the occurrence of ring-shaped nucleoli, micronucleoli or absence of nucleoli. Considering colocalization the pattern of galectin-3-binding sites coincided with the presence of desmosomal proteins such as desmoplakin-1 and desmoglein but not beta(1) integrin, a potential ligand. Interestingly, studied basal cell carcinomas expressed no binding sites for galectin-3, while a limited number of cells were DBA-reactive. CONCLUSION: The expression of galectin-3-binding sites and also DBA-reactive glycoligands correlates with an increased level of differentiation and/or cessation of proliferation in the examined squamous stratified epithelia. Further application of tissue lectins for characterizing ligand expression and its modulation is an important step to reveal functional relevance.
Keywords: galektin 3; Animals; antigen Ki-67; epitel; rostlinné lektiny; keratinocyty; Integrin beta1; Keratinocytes; Plant Lectins; vazebná místa; bazocelulární karcinom; desmoplakiny; Glycosylation; Keratins; vazba proteinů; Immunohistochemistry; cytoskeletální proteiny; buněčná diferenciace; lidé; Mice; Epithelial Cells; keratiny; prasata; desmogleiny; Protein Binding; kultivované buňky; myši; imunohistochemie; nádory kůže; Epithelium; Cells, Cultured; Cytoskeletal Proteins; Desmoplakins; Galectin 3; Skin Neoplasms; Swine; Desmogleins; glykosylace; Carcinoma, Basal Cell; Ki-67 Antigen; Cell Differentiation; zvířata; epitelové buňky; antigeny CD29; Binding Sites; Humans